KAPASITAS GESER BALOK PROFIL I FERRO FOAM CONCRETE - Nanda Mahathir; Mochammad Afifuddin; Abdullah Abdullah (Prodi Magister Teknik Sipil Unsyiah, 2021)
Lightweight concrete has a lower density than regular concrete. Foam concrete is one type of lightweight concrete. Aceh is one of the earthquake-prone provinces in Indonesia. Ferro foam concrete as a material to reduce the risk of earthquakes is an option. Ferro Foam Concrete is a composite material that combines wire mesh and foam concrete. Aside from its high load carrying capacity, lightweight, and ease of manufacture, this material have several advantages. Afifuddin et al. researched Canal Profile (C) configured to I using Ferro foam concrete (2013-2014). According to the findings of this study, the girder's weakness was that it experienced flexural failure during the test and that the ability of the girder as the I profile was not fully achieved due to the merging of two C profiles. The I profile does not fully achieve the size of the wings and body, which is calculated as an integral part of the I profile. As a result of this issue, the author wishes to conduct additional research on the subject. This research aimed to determine the shear capacity of the load-receiving system. The I Profile is the first of three samples to be created. BU 1 has three layers of wiremesh and measures 225 mm wide, 450 mm high, and 90 mm thick. BU 2 has four layers of wiremesh and measures 225 mm wide, 450 mm high, and 90 mm thick. Speciments 3 has four layers of wiremesh and is 300 mm wide, 600 mm high, and 120 mm thick. Reinforcement of test samples with D8 mm and D13 mm (steel screws) and wiremesh 3, 4, and 4 layers. SG 1.6 with FAS 0.4 and pozzolan at 10%. The results of the research on the shear capacity of the profile I 450-225-90-3L from the laboratory results were 11,855 tons, and from the theoretical obtained 12.007 tons. For the I profile of 450-225-90-4L, the laboratory results have a shear capacity of 12.730 tons. In comparison, the theoretical yield is 13.394 tons, and the shear capacity for the I profile of 600-300-120-4L is 21.150 tons and based on theoretical 24.462 tons.